Developing a Decision Support Framework for Tugboat Capacity Expansion: PT PIT’s Dual-Port Tugboat Operations - Nugraha, Cahyo Ady; Utama, Akbar Adhi (INOVASI, 2025)
Indonesia’s growing coal production has increased pressure on port logistics, particularly tugboat operations that are vital for barge maneuvering. PT PIT, the sole tug service provider for PTBA, currently operates with only two tugboats, resulting in limited capacity and increasing delays in coal shipments. This study aims to develop a decision support framework to optimize tugboat capacity expansion at PT PIT’s dual-port operations (Kertapati and Kramasan). A mixed methods approach is employed, combining quantitative modeling (queuing theory, financial feasibility, and project scheduling) with qualitative insights from stakeholder discussions. The analysis finds that expanding the fleet from two to four tugboats raises daily barge throughput from three to nearly ten, improves turnaround times, and increases PT PIT’s annual net revenue by approximately IDR 19.9 billion. Three procurement alternatives new purchase, operational lease, and financial lease are evaluated using the Analytical Hierarchy Process (AHP), with operational leasing emerging as the most viable due to its flexibility and lower risk. Risk assessment, following ISO 31000:2018 guidelines, identifies 15 critical risks, including capacity shortfalls and mechanical failures, with mitigation strategies proposed. The project is scheduled using PERT and Gantt methods, providing a roadmap for implementation by 2026. This integrated framework supports scalable, cost-efficient, and risk-mitigated logistics performance to meet Indonesia’s rising coal export demands.